Immediate Patient Satisfaction with Dental Esthetics After Endodontic and Prosthodontic Treatment of Dental Dyschromia - Adrian Jantea; Sorin Gheorghe Mihali; Dan Lolos; Anca Tudor; Roxana Oancea; Liliana Porojan (Dentistry Journal)
Objectives: This study aimed to evaluate patients’ satisfaction with the esthetic outcomes of combined endodontic and prosthetic treatments for devitalized or dyschromic teeth, a condition influenced by various intrinsic and extrinsic factors that present a growing concern in modern dentistry. Methods: A total of 104 patients, including 43 men and 61 women, underwent treatment using lithium disilicate restorations for esthetic zones and zirconium oxide restorations for regions with higher occlusal demands. Patient satisfaction was evaluated through a post-treatment questionnaire, classifying responses as either “satisfied” or “dissatisfied”. Dissatisfied participants were further asked to specify their concerns. Results: The study revealed a high satisfaction rate of 93%. Dissatisfaction was slightly more prevalent among women than men, but this difference was statistically insignificant. The primary reasons for dissatisfaction included darker restoration color, chipping, and gingival recessions. Conclusions: Combined endodontic and prosthetic treatments, utilizing lithium disilicate and zirconium oxide restorations, achieved high levels of patient satisfaction. Nevertheless, addressing specific issues, such as color matching and gingival health, could enhance outcomes further.